2010
DOI: 10.2460/ajvr.71.7.741
|View full text |Cite
|
Sign up to set email alerts
|

Associations of horse age, joint type, and osteochondral injury with serum and synovial fluid concentrations of type II collagen biomarkers in Thoroughbreds

Abstract: Horse age, osteochondral injury, and joint type all significantly affected type II collagen biomarker concentrations in SF and serum of Thoroughbreds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
4
17
3
Order By: Relevance
“…22,23 It has been suggested that there may be a fundamental difference in skeletal metabolism of osteoarthritis patients, compared with healthy individuals, that could affect biomarker concentrations. 24 Although unproven in the present study, this may be similar in horses because the present study found decreased serum concentrations similar to some other equine biomarker studies 14,18,25,26 of naturally occurring joint disease.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…22,23 It has been suggested that there may be a fundamental difference in skeletal metabolism of osteoarthritis patients, compared with healthy individuals, that could affect biomarker concentrations. 24 Although unproven in the present study, this may be similar in horses because the present study found decreased serum concentrations similar to some other equine biomarker studies 14,18,25,26 of naturally occurring joint disease.…”
Section: Discussionsupporting
confidence: 75%
“…It is not uncommon for younger horses to have higher biomarker concentrations than mature horses. 25 In the present study, no association between age and serum SDF-1 concentrations was found, but the association between age and biomarker concentrations may not be straightforward. 25 Ideally, osteoarthritis biomarkers should be investigated in multiple body fluids (serum, urine, and synovial fluid).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This is the first study in which the long-term consequences of an impact joint injury have been evaluated in STBRs with spontaneous PTOA, regularly trained after a rehabilitation period, and using biomarkers to assess disease activity. Previous studies focused on OA biomarkers in experimental horse models spread their observations to a limited number of weeks following the acute joint injury [2, 7, 27, 3840]. …”
Section: Discussionmentioning
confidence: 99%